Comparison of standard-dose 3-weekly cisplatin and low-dose weekly cisplatin for concurrent chemoradiation of patients with locally advanced head and neck squamous cell cancer: A multicenter retrospective analysis. Issue 21 (May 2018) - Lee, So Yeon; Choi, Yoon Seok; Song, Ik-Chan; Park, Sang Gon; Keam, Bhumsuk; Yang, Young Jun; Song, Eun-Kee; Lee, Hyo Jin; Cho, Sang-Hee; Shim, Hyeok; Park, Keon Uk; Lee, Ki-Hyeong; et al.
Abstract : Abstract: Standard treatment for locally advanced (stage III-IV) head and neck squamous cell cancer (LA-HNSCC) is concurrent chemoradiation therapy (CCRT) with cisplatin 100 mg/m 2 every 3 weeks. For medically unfit patients susceptible to treatment-related adverse events, low-dose weekly cisplatin (30–40 mg/m 2 ) can be used as an alternative. In this study, we retrospectively compared the therapeutic outcomes of low-dose weekly cisplatin regimen and standard regimen in CCRT for LA-HNSCC. The medical records of histologically confirmed LA-HNSCC patients were retrospectively reviewed from January 1, 2007 to December 31, 2012. Patients who were treated with CCRT as initial treatment were included. Among 220 patients eligible, 65 (29.5%) were treated with cisplatin dosing schedule of 100 mg/m 2 every 3 weeks and 155 (70.5%) with 30 to 40 mg/m 2 weekly. The overall response rate in 3-weekly group was 92.3% and did not differ from that in weekly group (91.0%). The median progression-free survival of the weekly group was not attained but was not significantly different from that of 3-weekly group (50.7 months, 95% confidence interval [CI] 42.2–59.1 months) ( P  = .81). Also, the median overcall survival did not differ significantly between 2 groups ( P  = .34). In the present study, low-dose weekly cisplatin showed therapeutic outcomes comparable to standard-dose cisplatin in CCRT for LA-HNSCC. Prospective comparison of standard-dose three-weekly and low-dose weekly cisplatin is warranted.